Fire retardancy behavior of polymer/clay nanocomposites - Zope, Indraneel Suhas (2017)
Polymer/clay nanocomposites show significant reduction in peak heat release rates (up to ~70 %) during combustion, which is instrumental in restricting the flame spread and subsequent fire growth. This makes clay a potential eco-benign flame retardant for polymers. However, majority of polymer/clay nanocomposites display lower ignition times, restricting their wide-spread usage. Though this is widely attributed to the catalytic reactivity of clay, this aspect is poorly studied so far. This essentially forms the basis of this work, which focuses on developing a detailed understanding of the influence of metal ions like Mg2+, Al3+, and Fe3+ that are inherent to clay structure on the decomposition behavior of organic matter (polymer and organic modifier). To accomplish the above objective, in the first part of study, montmorillonite (MMT, from smectite clay family) was enriched with these metal-ions by cation exchange process to amplify their concentration at exchange position. Their effect on decomposition behavior of organic modifier, hexadecyltrimethylammonium bromide (HDTMA+), and subsequently on combustion and thermo-oxidative decomposition behavior of polyamide 6 (PA6) matrix was evaluated. The second part of study focuses on the elucidating the catalytic activity of different smectite clays that are inherently and individually rich in one of these metal ions in their octahedral layer. Precisely, hectorite (rich in Mg2+), montmorillonite (rich in Al3+) and nontronite (rich in Fe3+) are used. It was observed that the catalytic activity of exchanged clays was a combined effect of Brønsted and Lewis acid characters associated with the metal ions. Brønsted acidity affected the initial stages of organic modifier decomposition, while Lewis acidity affected the oxidation stability of carbonaceous residue beyond clay dehydration temperatures. Mechanism of HDTMA+ decomposition is provided adding fundamental knowledge to the field of organically modified clays. Even in PA6 matrix, each metal ion uniquely influenced different stages of decomposition depending on its concentration, location and degree of clay dispersion. By evaluating both condensed phase and gas phase chemical compositions, the effect of metal ions on thermo-oxidative decomposition mechanisms for PA6 are proposed. Briefly, the presence of Al3+ accelerated (time and temperature of) decomposition during the initial stages, while Mg2+ rich composite displayed maximum thermo-oxidation stability and gave the highest char. Fe3+ has prominently altered the chemical composition of condensed phase during pre-ignition stages without having any noticeable effect on decomposition onset temperature. However, it also generated highest smoke. Further, the catalytic effect of clays followed a similar pattern even when the metal ions are situated in the octahedral layer (lattice sites). Hectorite containing PA6 showed highest charring tendency synonymous to MgMMT; while nontronite (similar to FeMMT) reduced oxidation stability of carbonaceous matter and generated more smoke. Last part of this work explores an avenue to restrict the interfacial interaction between clay surface and polymer matrix, virtually, making PCN combustion and decomposition independent of clay catalysis. To achieve this target, a simple route is proposed wherein organically modified clay was coated with high-temperature-resistant polymers like polyetherimide and polyimide using solution-suspension mixing. High glass transition temperatures/very high melting points of these coating polymers prevented direct contact between clay surfaces with neighboring decomposing PA6 matrix. This has led to prevention of (clay-catalysis assisted) early ignition while maintaining the unique advantage of polymer/clay nanocomposites i.e. reduction in peak heat release rate (~52 % as compared to the neat matrix). In conclusion, this is the first-of-its-kind report providing a holistic insight into the effect of individual metal ions inherently present in clays on thermo-oxidation and combustion behaviors of polymer/clay nanocomposites. A performance matrix was also generated that associates each metal ion with different combustion and decomposition properties like decomposition time/temperature, total decomposition enthalpy, smoke generation and char formation. This matrix can be utilized in design and development of clays to impart superior flame and fire retardant properties to polymer/clay nanocomposites.